Hubungan Kepercayaan Diri dan Dukungan Sosial dengan Kecemasan Mahasiswa Magister Psikologi Universitas Medan Area dalam Menyelesaikan Tesis - Anggiat Timbul Purba; Abdul Munir; Amanah Surbakti (Mahesa Research Center, 2022)
The purpose of this study is to find out the Correlations of Self-Confidence and Social Support with the Anxiety of Students of Master of Psychology Medan Area University in completing the thesis. This research is quantitative research Ex post pacto Correlational. The research population is a Master of Psychology student at Medan Area University who experienced anxiety in completing a thesis as many as 55 people. By using the Total Sampling Technique (the entire population becomes a sample of research). Data collection techniques are carried out on a scale (Self-Confidence, Social Support and Anxiety). The data analysis technique in this study is multiple regression analysis. From the results of multiple regression analysis, it is known that the first hypothesis there is a significant negative relationship between Self-confidence and Anxiety, judging from the value of the determinant coefficient (R) = -0.602, contribution of 36.2%. The second hypothesis is that there is a significant negative relationship between social support and anxiety in view of the value of the determinant coefficient (R) = -0.631, a contribution of 39.8%. And the third hypothesis shows that there is a significant negative relationship between Self-Confidence and Social Support with Anxiety judging by the value of the determinant coefficient (R) = -0.659 contributing 43.4%. Based on the results of the third study the hypothesis is acceptable.